The use of building blocks to develop visual motor and spatial abilities among the educable mentally retarded - Otsuka, Barbara Gibb 1946- (College of Education, University of the Philippines Diliman, 1977)
This study is an exploratory analysis of the feasibility of developing visual-motor skills and spatial abilities in the educable mentally retarded. A proposed training program that purported to stimulate the development of these abilities was tested. In a simple pre-test-post-test pre-experimental design, this proposed program was tested to see if students who used it would progress in the development of these abilities. The test was administered to the students in a class of EMR youth and adults. Three Filipino subjects with ages 13, 17, and 19, were then selected and tutored for three weeks using the proposed training program then the same test was administered. The results of the findings indicate that the training program had some effect on the subjects' awareness of spatial relations.